Extratos vegetais na propagação in vitro de Epidendrum ibaguense Kunth - Silva, Eliana de Souza e (2014)
The micropropagation of orchids is a technique used for various purposes, may be noted the rapid multiplication of plants, propagation of new hybrid, large-scale production and obtaining free arrays of pathogens. The use of natural extracts with antimicrobial activity in micropropagation shows up as an alternative, environmentally friendly and economical way to obtain plants free of microorganisms. This study aimed to evaluate the use of extracts of Allium sativum (garlic), Syzygium aromaticum (clove) and propolis to prevent contamination with micro-organisms during the process of in vitro subculture of Epidendrum ibaguense Kunth and the possible interference of these extracts on vegetative growth of seedlings. The microorganisms Aspergillus sp. Candida sp. Gram-negative bacteria, Gram-positive and Penicillium sp. present in the contaminated bottles with culture, derived from in vitro culture and the environment, were isolated and identified. We evaluated the antimicrobial activity of the extracts on the isolated microorganisms and it was observed that the extract of clove inhibited their growth. Seven compound treatments were used by Murashige; Skoog (1962) with half the concentration of macronutrients, plus charcoal and garlic extracts to 1.0 mgL-1 (T1), garlic 0.5 mgL-1 (T2), cloves 1.0 mgL- 1 (T3), cloves 0.5 mgL-1 (T4), propolis to 1.0 mgL-1 (T5), propolis 0.5 mgL-1 (T6) and control (T7) on a randomized complete randomized with five replications and three seedlings per replication. Sixty days of subculture in the media with the extracts evaluated the shoot height, the length of roots, number of roots, leaves number, the length of the longest leaf, the weight of the fresh weight, the weight of the mass drought and the multiplication rate of the seedlings. There were significant effects of the extracts of garlic, clove and propolis in the development of in vitro plantlets of E.ibaguense. Clove extract showed antimicrobial activity against microorganisms Aspergillus sp., Candida sp., Escherichia coli, Penicillium sp. and Streptococcus pneumoniae and the extracts of garlic and propolis showed no antimicrobial activity against any of the tested strains. Through this work, it was possible to establish a protocol for the in vitro cultivation of E. ibaguense for the contamination control.